THE ANALYSYS OF LEARNING ENGLISH ON YOUTUBE TO IMPROVE SPEAKING SKILL - Ikram Nur Amri Akbar; Baso Jabu; Chairil Anwar Korompot (State University of Makassar, 2023)
The goal of this study is to determine whether there is the students’ perception of the YouTube application improves their speaking skills in the second-semester academic year 2021-2022 of the English Education Study Program at the Faculty of Language and Literature State University of Makassar. Mixed quantitative and qualitative research methodologies were used. In order to fulfill the study's objectives, the information was gathered through an interview and a Likert questionnaire. The sample of the questionnaire is 30 students and Interviews of 10 students. The results of data analysis show that (1) positive student perceptions of the use of YouTube application in learning speaking skill with the classification, 12 (40%) students classified Strongly positive, (2) According to student explanations provided in interviews about their perspectives of using YouTube, it is a useful and entertaining online learning tool with good characteristics that greatly promote acquiring speaking skills in this age of pandemics. YouTube allows pupils to improve speaking skills despite the pandemic because it still allows for learning many speaking skill with lot of video content education and many native speakers. Keywords— Students Perception, YouTube, Speaking Skill